Post-mining landscape ecology - analysis of selected problems, the case of Adamów Brown Coal basin = Ekologia krajobrazu pogórniczego - analiza wybranych problemów na przykładzie Kopalni Węgla Brunatnego "Adamów" - Fagiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the main problems of the development of post-mining area landscapes, which are due to the ignoring or including, to a small extend, the environmental criteria in the process of reclamation. It refers to the newly shaped elements (forests, meadows, reservoirs, arable land), which create the ecological structure of post-mining landscape, and in particular their spatial distribution, structural and functional integrity with the areas not transformed by mining. On this basis, the principles of shaping the ecological structure of post-mining areas were formulated, which should become a code for good reclamation practice.
Keywords: krajobraz pogórniczy; ekologia krajobrazu; rekultywacja; post-mining landscapes; landscape ecology; reclamation